Activin‐A Regulates Bone Morphogenetic Protein Signaling in Pulmonary Endothelial Cells Without Affecting Bone Morphogenetic Protein Type‐II Receptor Expression - Benjamin J. Dunmore; Nobuhiro Kikuchi; Wei Li; Paul D. Upton; Nicholas W. Morrell (Pulmonary Circulation, 2025)
ABSTRACT Activin‐A is elevated in pulmonary arterial hypertension (PAH) patients, and reportedly suppresses BMPR‐II. This suggests one mechanism of action for PAH drug, sotatercept, an activin‐ligand trap. However, we were unable to confirm that activin‐A reduces BMPR‐II in pulmonary endothelial cells. Thus, it seems unlikely that sotatercept influences BMPR‐II or PAH via this mechanism.